Interprofessional education-relevant accreditation standards in Canada: a comparative document analysis - Mohammad Azzam; Anton Puvirajah; Marie-Andrée Girard; Ruby E. Grymonpre (BMC, 2021)
Abstract Background Increasing evidence suggests that sustainable delivery of interprofessional education (IPE) has the potential to lead to interprofessional collaborative practice (IPCP), which in turn has the potential to lead to enhanced healthcare systems and improved patient-centered care health outcomes. To enhance IPE in Canada, the Accreditation of Interprofessional Health Education (AIPHE) project initiated collaborative efforts among accrediting organizations of six health professions to embed IPE language into their respective accreditation standards. To further understand the impact of the AIPHE project, this study evaluated the accountability of the IPE language currently embedded in Canadian health professions' accreditation standards documents and examined whether such language spanned the five accreditation standards domains identified in the AIPHE project. Methods We conducted a comparative content analysis to identify and examine IPE language within the "accountable" statements in the current accreditation standards for 11 Canadian health professions that met our eligibility criteria. Results and discussion A total of 77 IPE-relevant accountable statements were identified across 13 accreditation standards documents for the 11 health professions. The chiropractic, pharmacy, and physiotherapy documents represented nearly 50% (38/77) of all accountable statements. The accountable statements for pharmacy, dentistry, dietetics, and nursing (registered) spanned across three-to-four accreditation standards domains. The remaining nine professions' statements referred mostly to "Students" and "Educational program." Furthermore, the majority of accreditation standards documents failed to provide a definition of IPE, and those that did, were inconsistent across health professions. Conclusions It was encouraging to see frequent reference to IPE within the accreditation standards of the health professions involved in this study. The qualitative findings, however, suggest that the emphasis of these accountable statements is mainly on the students and educational program, potentially compromising the sustainability and development, implementation, and evaluation of this frequently misunderstood pedagogical approach. The findings and exemplary IPE-relevant accountable statements identified in this paper should be of interest to all relevant stakeholders including those countries, where IPE accreditation is still emerging, as a means to accelerate and strengthen achieving desired educational and health outcomes.